Pengaruh Ukuran Perusahaan, Laba Operasi, Solvabilitas Dan Komite Audit Pada Audit Delay - Sari, Ayu Puspita; Widhiyani, Luh Sari (E-Jurnal Akuntansi, 2015)
The development of capital markets firms indicate the number of requests for audits of financial statements that is a source of information for stakeholders.Good financial statements has an appeal that can increase the price of the stock market. The Company requires the issuance of the financial reporting process faster for the company to have a good image in the eyes of the public. The samples used were 60 companies. Nonprobability sampling method by using purposive sampling method was used in this study. Methods of data collection in the form of non-participant observation method, the linear analysis techniques. Obtain partial test (1) the size of the company negatively affect audit delay, (2) operating profit negatively affect audit delay, (3) solvency positive effect on audit delay, and (4) the audit committee has no effect on audit delay.
Keywords: firm size, operating profit, solvency, audit committee, audit delay